Arx revisited: involved in the development of GABAergic interneurons - Akio Tsuboi; Seiich Yoshihara (Frontiers in Cell and Developmental Biology)
The aristaless-related homeobox (Arx) transcription factor, located on the X chromosome, has been implicated in a wide range of neurological disorders, including intellectual disability and epilepsy, as well as diabetes and pancreatic developmental disorders. In the mouse brain, Arx is expressed not only in the olfactory bulb (OB) and cerebral cortex progenitor cells but also in these gamma-aminobutyric acid (GABA)-releasing interneurons. In the initial study, constitutive Arx knockout (KO) mice showed aberrant migration and a reduction in GABAergic interneurons in the neonatal OB. However, constitutive Arx KO mice with perinatal lethality preclude further analysis in adolescent or adult mice. To overcome this, Arx-floxed mice have been crossed with Cre driver mice to generate conditional KO mice with selective Arx deletion in distinct interneuron progenitors. These studies have identified Arx as a key transcriptional regulator involved in the generation, fate determination, and migration of cortical interneurons. This review focuses on the critical role of Arx in the development of progenitor cells and the migration of interneurons in the mouse OB and cerebral cortex, and discusses differences in Arx mutant-based abnormality between mouse mutants and human patients.